Outcomes of Chronic Turf Toe Repair in Non-athlete Population: A Retrospective Study - Pinter, Zachariah W. (Indian J Orthop, 2020)
BACKGROUND: Turf toe injuries, though most common in athletes, can also occur in non-athletes. No study exists in the current literature investigating operative outcomes in non-athlete patients with chronic turf toe injury. In this study, we present our outcomes on operatively treated turf toe injuries in non-athletes in the only cohort yet studied. METHODS: Using ICD-10 codes, we assembled a cohort of 12 patients who underwent operative repair of chronic turf toe injury from January 2012 through January 2018 at the investigating institution. These 12 patients were evaluated to determine demographic information, method of injury, length of time from injury to surgery, clinical and radiologic characteristics of the injury, and operative outcomes including mean preoperative and postoperative VAS (Visual Analog Scale) scores, preoperative and postoperative FFI (Foot Function Index) scores, and postoperative complications. RESULTS: On initial clinical presentation, all 12 patients had local tenderness with associated painful range of motion. Four patients had restricted range of motion, all patients had a positive Lachman test, two had local edema, and eight had hallux valgus deformity. Mean VAS improved from 4.6 (range 2–9) to 1 (range 0–4). Mean FFI improved from 102.5 (range 56–177) to 61.75 (range 23–144). All patients had a negative Lachman test at final follow-up. No patients developed major complications or required revision surgery. CONCLUSIONS: Our study is the first to investigate operative outcomes following chronic turf toe injury in non-athlete patients. Based on our study, surgeons and patients can expect significant improvement in overall pain and function following surgery.